Serving Leadership in Relation to Job Satisfaction of Civil Servants at the National Police (PNPP) at the South Tangerang Police Resort Nasri1, Lalu Hedwin - Nasri Nasri; Lalu Hedwin Hanggara; Amril Muhammad (Budapest International Research and Critics University, 2022)
This study time to determine the relationship between leadership and job satisfaction at Civil Servants at the National Police (PNPP), South Tangerang Resort Police. A total of 233 respondents were sampled according to the Slovin formula. The reliability of data collection and validity checks of questionnaires with product-moment correlations was calculated using the Cronbach-Alpha formula. Technical statistical analysis of hypothesis testing was performed using Pearson's Product Moment Correlation with the application SPPS version 11.0. The results of this study showed that the correlation was 0.631, and the t-test results showed that the correlation was significant. Calculating a coefficient of determination of 0.3982 indicates that PNPP's job satisfaction at South Tangerang Police Station is 39.82% influenced by on-the-job leadership.